Using Auschwitz Prisoner Numbers to Correct Deportation Lists - Jean-Pierre Stroweis (Genealogy, 2024)
A list of the first Jews deported from Compiègne, France on 27 March 1942 to Auschwitz-Birkenau was never found. Similarly, there is no known arrival list for this convoy. All the 1112 men entered the camp, were assigned prisoner numbers, and were then tattooed. In 1978, Serge Klarsfeld created a list by assembling sub-lists from WWII and immediate post-war sources. Despite significant ongoing research by Klarsfeld and others, no definitive list was ever compiled. Material recorded and maintained by the Nazis (daily count book, death registers, entry cards) pertaining to this early period does exist. This paper demonstrates how systematic use of Auschwitz prisoner numbers combined with French censuses and metrical records enabled us to significantly revise our records of who was deported in this transport, by eliminating dozens of names, amending many more, and adding several others.